Beyond syndicated loans : sources of credit for developing countries - Shilling, John D. (Washington, D.C. : World Bank, 1992)
This paper present a good overview for those interested in the variety of instruments available in the world capital markets, and they offer hope that developing countries can again access external credit after the near complete demise of voluntary syndicated lending.
Includes bibliographical references.
osa 02/11/2016
Ref
Keywords: Investment, foreign - developing countries; Loans, foreign - developing countires